Long-term unemployment and subsidizing vacancies in a growth-matching model - Angela Birk (Hamburg Institute of International Economics (HWWA), 2001)
How can long-term unemployment be reduced by policy measures of the government? In this paper a growth-matching-model is developed, in which the unemployment pool consists of heterogeneous unemployed workers, short-term and long-term unemployed, and with an endogenous skill-depreciation of the long-term unemployed emerging as technical progress accelerates. For innovation countries characterized by rapid technical progress we show that through subsidizing vacancy creation which causes a substitution and an income effect long-term unemployment can be reduced. Since the positive substitution effect implied by subsidizing vacancy creation outweighs the negative income effect induced by taxing the household's income, a positive employment effect results leading to additional job-matches and decreasing unemployment duration. Therefore, the introduction of subsidies will be favorable for achieving a reduction in long-term unemployment. – – Wie kann die Langzeitarbeitslosigkeit durch geeignete Politikmaßnahmen des Staates reduziert werden? In diesem Artikel wird ein Wachstums-Matching-Modell entwickelt, das durch heterogene Arbeitslose - Kurz- und Langzeitarbeitslose - und bei steigendem technischen Fortschritt durch die endogene Abwertung von Fähigkeiten und Fertigkeiten der Langzeitarbeitlosen charakerisiert ist. Für Innovationsländer, die mit akzelerierendem technischen Fortschritt konfrontiert sind, wird gezeigt, dass die Subventionierung von Vakanzen, bei der sowohl ein Substitutions- wie auch ein Einkommenseffekt entsteht, eine Reduzierung der Langzeitarbeitslosigkeit impliziert. Da der positive aus der Vakanzsubventionierung resultierende Substitutionseffekt den negativen Einkommenseffekt, der durch die Besteuerung der Einkommen verursacht wird, überwiegt, wird ein positiver Beschäftigungseffekt generiert. Dieser positive Beschäftigungseffekt führt zu zusätzlichen Job-Matchings und sinkender Arbeitslosigkeitsdauer. Somit kann der Staat mit Hilfe der Subventionierung von Vakanzen, eine Verringerung der Langzeitarbeitslosigkeit erreichen.
Keywords: J41; E24; O41; 330; long-term unemployment; growth; search; matching; subsidies; Langzeitarbeitslosigkeit; Arbeitsmarkttheorie; Technischer Fortschritt; Arbeitsnachfrage; Subvention; Offene Stellen; Matching; Wachstumstheorie; Beschäftigungseffekt; Theorie